The effect of inside outside circle (IOC) model by using flashcards towards students’ English vocabulary mastery - Rizki Ani Khairunnisa; Agrissto Bintang Aji Pradana; Aditia Eska Wardhana (Erudita: Journal of English Language Teaching, 2021)
This research aims to determine the effect of Inside Outside Circle (IOC) model by using flashcards on students’ English vocabulary mastery. This research was done on the 3rd-grade students of one elementary school in Magelang Regency, Central Java, Indonesia. This research used Pre-Experimental Design which type is One Group Pretest Posttest Design through one kind of treatment. The samples in this research were 3rd-grade students as many as 20 students. The data collection method was a multiple-choice test. The instrument test of this research was a validity test by experts (expert judgment), they are English lecturers of a private university Magelang and a 3rd-grade teacher of elementary school in Magelang Regency.  The results of this research pointed out that there was a positive effect of the Inside Outside Circle (IOC) model by using flashcards on students’ English vocabulary mastery. The effect was shown by pre-test and post-test results with means 49 and 80. The result of the Wilcoxon test showed that the significance of Z value was -3,725 with Asymp. Sig. (2-tailed) 0,000 < 0,050.